Determinants of Customer Revisit Intention on Cafe in East Jakarta - Rahmadila Alif Madia Putri; Atik Aprianingsih (Management Analysis Journal, 2025)
The purpose of this research is to determine the influence of marketing mix 7Ps on customer revisit intention while mediating customer satisfaction as a valuable advancement contribution to cafe industry in Indonesia. The research uses quantitative methodology using online survey with questionnaire that distribute to respondents. The methods used are Multiple linear regression analysis and Importance Performance Analysis, allowing researchers to investigate the influence between relevant variables. Total valid respondents are 226 Kedai Malabar loyal customers. The sample selection used a nonprobability purposive sampling technique with customers as population, loyal customers who are aged >20 years and have visited Kedai Malabar at least twice a year as samples. The results show that product, place, price, process, people, and physical evidence positively and significantly affect customers’ revisit intention. In contrast, the promotion does not has an significant effect impact on customer satisfaction for Kedai Malabar's revisit intention. To increase customer satisfaction, an IPA analysis found that Malabar should focus on improving physical evidence, place, price, and people variables.